2019
DOI: 10.1186/s40359-019-0359-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of clinically important improvements in occupational and quality of life outcomes among mental health service users after completion and follow-up of a lifestyle intervention: multiple regression modelling based on longitudinal data

Abstract: BackgroundBalancing Everyday Life (BEL) is a new activity-based lifestyle intervention for mental health service users. An earlier study found BEL to be effective in increasing occupational engagement, occupational balance, activity level, and quality of life scores when compared with a care-as-usual group. However, it is unclear whether care context and socio-demographic, clinical and self-related factors at baseline also influence the results. Thus, the aim of the current study was to explore whether such fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Occupational balance is defined as the state in which there is a positive evaluation between the number of occupations and their variations [1]. Traditionally, and from an intrapersonal perspective, occupational balance has been described as a satisfactory pattern that the subject presents when carrying out their occupations [2][3][4]. Occupations are defined as all types of life activities in which people, groups, or populations participate, including activities of daily living, instrumental activities of daily living, rest and sleep, education, work, play, leisure, and socializing [5].…”
Section: Introductionmentioning
confidence: 99%
“…Occupational balance is defined as the state in which there is a positive evaluation between the number of occupations and their variations [1]. Traditionally, and from an intrapersonal perspective, occupational balance has been described as a satisfactory pattern that the subject presents when carrying out their occupations [2][3][4]. Occupations are defined as all types of life activities in which people, groups, or populations participate, including activities of daily living, instrumental activities of daily living, rest and sleep, education, work, play, leisure, and socializing [5].…”
Section: Introductionmentioning
confidence: 99%
“…(8)(9)(10)(11)(12)(13)(14). With this aspect, our results also lay the groundwork for the necessity of occupational therapy interventions to be developed to overcome this negative effect on university personnel who have had COVID-19 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). This study, which compares the experiences of personnel who have COVID-19 infection and who work remotely for precautionary purposes during the quarantine period, and other personnel who continue to work in the office environment, was carried out to investigate the topics that will draw attention to the difference in the working environment during the pandemic period (25)(26).…”
mentioning
confidence: 59%
“…Occupational balance can also be defined as the situation where there is a positive distribution between the number of occupations and occupational areas (12). A person with occupational balance can be defined as a person who is satisfied with the balance in their living spaces and achieves well-being (13)(14)(15). Factors such as life satisfaction and quality can affect the maintenance of this balance by preventing access to resources necessary for subjective health (16,17).…”
mentioning
confidence: 99%
“…Supporting engagement in meaningful activities has been used to mitigate the negative effects of childhood adversity on mental health and psychological wellbeing in young adults (Oliver et al, 2006). In a range of populations, including university students (Eakman, 2014) and mental health service users (Hultqvist et al, 2019), meaningful activity engagement has been shown to improve life satisfaction, which is negatively impacted by childhood adversity (Booth et al, 2015). However, childhood adversity does not independently affect life satisfaction, as the effect of childhood experiences is moderated by sensory processing sensitivity (Greven et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further research exploring these constructs is also warranted in specific clinical populations who report low levels of meaningful activity engagement and/or high levels of childhood adversity. Research should particularly focus on people with mental health concerns, given their high rates of childhood adversity (Nurius et al, 2012), limited engagement in meaningful activities (Hultqvist et al, 2019) and diminished life satisfaction (Nurius et al, 2012).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%